Smoking habits of UK military personnel on deployment: Exercise SAIF SAREEA 3. Issue 6 (27th May 2020) - Williams, J F; Fuller, M; Smith, M B
Abstract : Introduction: Changes of environment brought about by deployments are often attributed to an increase in smoking of service personnel. Electronic cigarettes are recognised as being a viable aid to quitting smoking but are currently banned from sale in Oman and were therefore banned during exercise SAIF SAREEA 3 (SS3). This paper sought to establish whether smoking increased on this exercise and for what reasons. Also, if deployed smoking cessation services are likely to be used, if available. Methods: Questionnaires were distributed to deployed troops at various locations in theatre for data collection. Results: Smoking prevalence increased by 5.2% (29) in the deployed population by the end of the exercise. The largest increase was seen in those smoking 20 cigarettes a day or more, rising by 269.8% (73) with a mean increase of 9 cigarettes per day. During the exercise the number of personnel using electronic cigarettes decreased and individuals' rate of electronic cigarette use also decreased. Those who smoked less during the exercise did mainly through choice (56.8%). 50% (280) of all individuals who increased smoking habits during the exercise did so out of boredom. Conclusions: During exercise SS3 the number of individuals who smoked and the quantity they smoked increased. The ban on electronic cigarettes in Oman and while on exercise potentially had an effect on the increased smoking habits. There is an argument to include smoking cessation material in medical modules to prevent ex-smokers from restarting, continue to aid those quitting and potentially lessen severity of increasing smoking habits while deployed.